The effects of a novel high intensity exercise intervention on established markers of cardiovascular disease and health in Scottish adolescent youth - Duncan S. Buchan; John D. Young; Alan D. Simpson; Non E. Thomas; Stephen-Mark Cooper; Julien S. Baker (SAGE Publishing, 2012)
This study examined the effects of high intensity exercise on physical fitness components and cardiovascular disease (CVD) risk factors in youth. Forty-one participants (15-17 years) were divided into a control and an intervention (high intensity exercise, HIT) group. The HIT group (15 boys, 2 girls) performed three weekly sessions over seven weeks consisting of either four to six repeats of maximal sprint running with 20-30 s recovery. The control group (20 boys, 4 girls) continued their normal activity patterns. All participants had indices of obesity and blood pressure (BP) recorded in addition to four physical performance measures pre-and post-intervention: cardiorespiratory fitness, muscular power, sprint speed and agility. In the HIT group, significant improvements in cardiorespiratory fitness (P<0.01) and agility (P<0.05) were noted. Participants in the control group, meanwhile, experienced a significant decrease in counter movement jump performance. These findings demonstrate that brief, intense exercise interventions are useful for improving indices of physical fitness in a short period of time.